2012
DOI: 10.1007/s00405-012-2325-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of the Onodi cell with the variation of perisphenoidal structures

Abstract: The presence of the Onodi cell (OC) may be accompanied by morphological variations of the neighboring anatomic structures. Such variations carry significant surgical implications and challenges. Pneumatization of the sphenoid sinus induces anterior clinoid pneumatization (ACP), affects the type of the Vidian nerve (VN) canal or alters the courses of the internal carotid artery (ICA), and the optic nerves (ONs) are strongly depending on it. Onodi cell pneumatization may reach and surround the optic nerve in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 14 publications
6
25
2
3
Order By: Relevance
“…An Onodi cell may modify the surrounding anatomic structures, but it usually does not determine an alteration of the intrasphenoidal course of the vidian canal, being however significant as related to the anterior clinoid pneumatization 19 . When Onodi cells are present, the sphenoid sinus ostium shows tendency to be located inferiorly to a level observed in the absence of Onodi cells 20 .…”
Section: Resultsmentioning
confidence: 99%
“…An Onodi cell may modify the surrounding anatomic structures, but it usually does not determine an alteration of the intrasphenoidal course of the vidian canal, being however significant as related to the anterior clinoid pneumatization 19 . When Onodi cells are present, the sphenoid sinus ostium shows tendency to be located inferiorly to a level observed in the absence of Onodi cells 20 .…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of the Onodi cell differs greatly when comparing past studies. In studies based on CT, Onodi cell incidence is mostly low (8‐24%) . However, in their detailed study based on sagittal CT, Tomovic et al reported that the incidence of the Onodi cell was 65.3%, although they did not provide details about their method of identification.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference has been found in terms of the presence of sphenoethmoidal cells in patients with chronic rhinosinusitis compared to normal controls. 9 The optic nerve protruded into 80 per cent of sphenoethmoidal cells compared to only 18 per cent of normal sphenoid sinuses ( p < 0.01). In a study of 999 CT scans, sphenoethmoidal cells were identified in 16 per cent of cases and were bilateral in two-thirds of cases, as indicated by a characteristic cruciform appearance on coronal CT images (Figure 4).…”
Section: Case Fourmentioning
confidence: 92%